Forage sources in total mixed rations early in life influence performance, metabolites, and behavior of dairy calves - Toledo, A. F.; Dantas, J. G.; Barboza, R. D.F.; Tomaluski, C. R.; Oliveira, I. C.R.; Carvalho, N. I.; Marino, E. D.; Polizel, D. M. [UNESP]; Miller-Cushon, E. K.; Bittar, C. M.M. (American Dairy Science Association, 2024)
The objective of this study was to evaluate effects of forage inclusion and sources on performance, metabolism, and feeding behavior of dairy calves. Forty-eight Holstein calves were blocked and randomly assigned to 1 of 4 dietary treatments according to sex and BW at 28 d of life to determine the effects of feeding forage sources (ensiled and dry), with different quality on performance, metabolites, and behavior. Treatments consisted of a no-forage coarsely ground starter (CON); or total mixed ration (TMR) containing 7.5% on a dry matter (DM) basis of Tifton hay of either medium quality (MH) or low quality (LH); or 10% on a DM basis of corn silage (CS). During the first 28 d of life, all calves received 3 L of whole milk twice daily, a commercial pelleted starter and no forage, and water ad libitum. After that, the solid diet was changed to the respective dietary treatments. Calves were gradually weaned from 52 to 56 d of age, and followed for 14 d postweaning. Individual solid feed and milk intakes were recorded daily, and BW and metabolic indicators of intermediate metabolism were recorded weekly. Behavior was recorded, and the analysis was conducted on wk 7 (preweaning) and 10 (postweaning). Solid feed intake increased at wk 7 and 8 when MH, LH, and CS were included in TMR; the same results were observed postweaning. The diets did not affect the average daily gain and BW, but the feed efficiency increased with the CON diet. The β-hydroxybutyrate concentration was greater in calves receiving TMR-containing forage than CON diet. Furthermore, calves supplemented with forage had a greater rumination time. In conclusion, all forage sources included in the TMR showed feed intake and behavior benefits, reinforcing the need for fiber from forage in pre- and postweaning diets.
Keywords: effectiveness; fermented forage; particle size; total mixed ration